THE OBLIGATIONS OF THE FUNCTIONALITY OF SOCIAL INSTITUTIONS IN INDUSTRIAL SUGGESTIONS - Литовченко, І. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2018)
Stattia is privy to social and philosopher dosleness of the special functions of the social and economic institutions in the minds of becoming and developing an industrial suppository. It is shown that in the social and economic reforms the real estate and welfare of the people are characterized by the social and economic development of the system of co-tional institutions. Suttievich peretvoren zazyayut sphere vibrobitvtva, politichnі інститути, інститути управління, науки, релігії, освіти, сім`ї, які take on yourself the functions of social control and regulation of societal zv’yakvіv ta vіdnosin, and takozh zadavlenya nayvazhlivshih needs of members of suspilstva.